2017
DOI: 10.1080/09720073.2017.1351514
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cardiorespiratory Fitness and Anthropometric Variables among School-going Adolescents in Nigeria

Abstract: The increase in physical activity (PA) levels has been known to be associated with improved cardiorespiratory fitness status which helps in reducing the risk factors of non-communicable disease. However, the interaction between cardiorespiratory fitness and anthropometric variables remains unclear and needs further investigation. This study assessed the relationship between cardiorespiratory fitness and anthropometric variables among school-going adolescents in Nigeria. Two hundred and fifty apparently healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
5
1
1
Order By: Relevance
“…This finding is in agreement with other studies [ 29 , 30 ]. The correlation between children's height and CRF was statistically negatively significant, in contrast to what other studies suggest [ 31 , 32 ]. Α possible explanation for this difference could be the age range used in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in agreement with other studies [ 29 , 30 ]. The correlation between children's height and CRF was statistically negatively significant, in contrast to what other studies suggest [ 31 , 32 ]. Α possible explanation for this difference could be the age range used in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Body weight is a major confounder to performance on the field tests investigated (Pate et al, 1993). Body weight, height, gender, and body mass index are good CRE predictors among school students (Olawale, Mwila, Marie, & Lamina, 2017). Further, Vale et al, (2011) finding suggested that low CRE was a strong predictor of risk values of abdominal obesity in adolescence.…”
Section: Resultsmentioning
confidence: 95%
“…Based on the physiological concept, gender and age are potential confounders of the correlation between nutritional status and fitness level. [24][25][26][27] Besides being associated with the level of fitness, age and gender are also associated with nutritional status. Therefore, a confounding analysis for gender and age was carried out independently on nutritional status and fitness level in this study.…”
Section: Discussionmentioning
confidence: 99%